Desain Bisnis Model Canvas (BMC) Pada Usaha Batik Kota Madiun - Warnaningtyas, Hartirini (Universitas Merdeka Madiun, 2020)
Abstractâ€” This study aims to design a batik business strategy using Business Model Canvas. This type of research used in this research is descriptive with a qualitative approach. The location of the study was conducted in the city of Madiun. The selection of key respondents was conducted purposively by considering factors of understanding of the strategy carried out by the company, understanding of the company's condition, understanding of the company's internal conditions, understanding of the company's business model, understanding of the company's main competitors. The analysis techniques used are internal and external environment analysis, SWOT analysis, and Business Model Canvas. The results showed that the analysis of the internal and external environment produces an alternative strategy Strength-Opportunity as a strategy using strengths to take advantage of existing opportunities, Weakness-Opportunity as a strategy to fix internal weaknesses by using external opportunities, Strength-Threat as a strategy using internal strengths to avoid external threats , Weaknesses-Threat is the most defensive strategy, avoiding threats and minimizing weaknesses. Batik Kota Madiun requires improvements to its business model, namely the addition of six blocks, namely Key Partnership, Key Activities, Value Proposition, Customer Sement, Channel, Cost Structure, and Revenue Streams.Â Keywordsâ€”: Business Model Canvas (BMC); SWOT Analysis.